2021
DOI: 10.1186/s13567-020-00883-w
|View full text |Cite
|
Sign up to set email alerts
|

PEDV infection in neonatal piglets through the nasal cavity is mediated by subepithelial CD3+ T cells

Abstract: Porcine epidemic diarrhea virus (PEDV) primarily infects neonatal piglets causing catastrophic effects on the global pig farming industry. PEDV infects piglets through the nasal cavity, a process in which dendritic cells (DCs) play an important role. However, neonatal piglets have fewer nasal DCs. This study found that subepithelial CD3+ T cells mediated PEDV invasion through the nasal cavity in neonatal piglets. PEDV could replicate in the nasal epithelial cells (NECs) isolated from the nasal cavity of neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…At present, the identification of PEDV is mainly through the collection and detection of pig serum, pig intestine contents or pig feces. To the best of our knowledge, the fecal-oral route is believed to be the primary mode of PEDV transmission (Li et al 2018;Lin et al 2016;Yuan et al 2021). Moreover, virions in feces are frequently indirectly transmitted within and between pigpens via transport trailers, farm workers' hands, boots and clothes (Jung et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the identification of PEDV is mainly through the collection and detection of pig serum, pig intestine contents or pig feces. To the best of our knowledge, the fecal-oral route is believed to be the primary mode of PEDV transmission (Li et al 2018;Lin et al 2016;Yuan et al 2021). Moreover, virions in feces are frequently indirectly transmitted within and between pigpens via transport trailers, farm workers' hands, boots and clothes (Jung et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most existing studies of PED have focused on its pathogenesis via the fecal-oral route [4]; however, fewer studies have been conducted to delineate the underlying mechanisms of the fecal-nasal route. The nasal cavity is a route of entry for intestinal-infection-causing PEDV in piglets, while the migration of CD3 + T cells carrying PEDV plays an important role in PEDV infection through this route [7,8]. We demonstrated that PEDV could somehow be contained in the cytoplasm of CD3 + T cells.…”
Section: Discussionmentioning
confidence: 75%
“…Finally, virus-loaded CD3 + T cells reach the intestines via blood circulation, leading to intestinal infection through cell-to-cell contact [7]. A recent study reported that subepithelial CD3 + T cells mediated PEDV infection through the nasal cavity in neonatal piglets [8]. However, this report did not reveal a detailed mechanism by which CD3 + T cells transmit PEDV to the intestines via blood circulation.…”
Section: Introductionmentioning
confidence: 74%
“…Therefore, as the first site directly exposed to inhaled pathogens, the nasal epithelium is exploited by various viruses for viral entry, such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza virus, and respiratory syncytial virus ( 1 3 ). Like SARS-CoV-2, another enteric infectious coronavirus, porcine epidemic diarrhea virus (PEDV), exhibits tropism to nasal epithelial cells (NECs) and can cause diarrhea and dehydration in suckling piglets through nasal infection ( 4 , 5 ). However, the mechanism by which the virus enters the bloodstream from the nasal epithelium remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…PEDV primarily infects small intestinal epithelia, causing villous necrosis and atrophy. In addition to the fecal-oral route, the fecal-nasal route is another route of PEDV transmission through airborne aerosolized PEDV particles ( 4 , 5 ). Infectious PEDV presents in serum or blood cells in piglets infected with PEDV ( 13 , 14 ), suggesting that the virus possesses the ability to cross the endothelial barrier and cause viremia.…”
Section: Introductionmentioning
confidence: 99%